2019
DOI: 10.1109/access.2019.2902429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Competitive Features Using Deep Convolutional Neural Network for Finger Vein Recognition

Abstract: Deep convolutional neural networks (DCNN) have been applied successfully for finger vein recognition and have achieved promising performance in the past three years. However, public finger vein datasets are scarce and tend to be relatively small, and thus unable to provide a substantial number of welllabeled images needed to train an effective convolutional neural network (CNN). In this paper, a CNN model pre-trained on ImageNet is adopted to develop a CNN-based local descriptor named CNN competitive order (CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…If the big data technology is applied to the music intelligent management system, it can assist the music intelligent management system to realize the active recommendation function, which is also a relatively new way [9]. e deep convolutional neural network technology (CNN) in big data technology can better complete the data mapping relationship [10,11]. If deep CNN technology is used to map the relationship between music lovers' behavior and living environment and the music intelligent management system, it can improve the function of the music intelligent management system, which is also a better application direction.…”
Section: Introductionmentioning
confidence: 99%
“…If the big data technology is applied to the music intelligent management system, it can assist the music intelligent management system to realize the active recommendation function, which is also a relatively new way [9]. e deep convolutional neural network technology (CNN) in big data technology can better complete the data mapping relationship [10,11]. If deep CNN technology is used to map the relationship between music lovers' behavior and living environment and the music intelligent management system, it can improve the function of the music intelligent management system, which is also a better application direction.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the results of different configurations of the Light CNN (LCNN) and the VGG-16 models. On the other hand, Lu et al [ 121 ] presented the CNN competitive order (CNN-CO) local descriptor, which is generated by using a CNN that is pre-trained on ImageNet. After selecting the effective CNN filters from the first layer of the network, the CNN-CO computes the CNN-filtered images, builds the competitive order image, and, lastly, generates the CNN-CO pyramid histogram.…”
Section: Feature Extraction Vs Feature Learningmentioning
confidence: 99%
“…Where ℎ , denoted as the lower half of the original input finger vein image size. Then, the preprocessing filtering mask is constructed based on using (11) and (12)…”
Section: Globalized Finger Vein Lines Extraction Based (Gmfpi)mentioning
confidence: 99%
“…Yu at el. [11] proposed a convolutional neural network (CNN) based local feature descriptor for finger vein recognition. The proposed system showed that the convolutional neural network based local feature descriptor (CNN-CO) can exploit and extract the discriminative finger fine features.…”
Section: Introductionmentioning
confidence: 99%